Pulmonary arterial pseudo-aneurym secondary to pulmonary mucormycosis - Nitin P. Ghonge; Nidhi Goyal; Nikhil Modi (The Journal of Association of Chest Physicians)
Pulmonary mucormycosis is a rapidly progressive, angio-invasive fungal infection with high morbidity and mortality, particularly in immunocompromised and diabetic patients. Pulmonary artery pseudoaneurysm is a rare but life-threatening complication of pulmonary mucormycosis. We report a case of a 62-year-old diabetic male presenting with acute hemoptysis, who was diagnosed with pulmonary mucormycosis complicated by a pseudoaneurysm of the left lower lobe pulmonary artery. Prompt endovascular coil embolization followed by antifungal therapy and surgical lobectomy led to successful management and favorable outcomes. This case highlights the importance of early recognition, imaging, and multidisciplinary treatment strategies in managing such complex presentations.